MEASURING FINANCIAL PERFORMANCE OF AIRLINE PASSENGER TRANSPORT COMPANY IN EUROPEAN - Dayi, Faruk; Esmer, Yusuf (International Institute of Social and Economic Sciences, 2017)
Airline passenger transport draws attention as a rapidly growing sector in the passenger transportation. In our country (in Turkey), the first in 1933, Turkish Airlines Corporation (THY) was established and today it is seen that the activity of the 10 companies in sector of airlines in Turkey. According to the results of Skytrax passenger evaluation, Turkish Airlines is award for 6 years (2011-2016) as the best airline in Europe seems worthy. In fact, the main reason behind this success can be the presence of a strong financial structure. Therefore, the main aim of this study is to evaluate the success of THY. For this reason, airline companies, which are operating a leading position in Europe, and THY is needed comparison of the results. In our study, datas that seven airline companies operating in Europe are used their financial statements including 2011-2016 periods. According to the results of analysis, Air Berlin Group and Thomas Cook Group have the highest loss in implementation. In addition, It is seen that Lufthansa and Turkish Airlines have the successful performance.
Keywords: 9. Industry and infrastructure; 8. Economic growth; 11. Sustainability